The black hole of empire : history of a global practice of power - Chatterjee, Partha (PERMANENT BLACK, 2013)
When Siraj, the ruler of Bengal, overran the British settlement of Calcutta in 1756, he allegedly jailed 146 European prisoners overnight in a cramped prison. Of the group, 123 died of suffocation. This title follows the ever-changing representations of this historical event and founding myth of the British Empire in India. Read less